Current Situation in Syria (January-March 2012) - Momynkulov, Zh. B. (Journal of Oriental Studies, 2016)
In this article issues related to the current situation in Syria are considered. In the beginning of the paper general review of the most important events and changes, which took place in the last period in Syria, is given. But the efforts of the geopolitical powers turned to be insuffi cient for peaceful and forehanded regulation of the Syria crisis. Position of Russia and China regarding the issue remains unchanged, what is regularly criticized by the West States. Open position of US and Israel in this issue doesn`t cause any diffi culty to the experts. But, positions of Turkey, China, Iran and Arab Countries League require very attentive attitude and approach for the better understanding of their policies in the Middle East Region. Current situation in Syria still remains uncertain. This is why it`s diffi cult to make any precise prognosis in regard to the prospects of possible changes in Syria.